A risk professional's survival guide applied best practices in risk management - Rossi, Clifford., author (Hoboken, New Jersey Wiley, 2014)
Balanced, practical risk management for post - financial crisis institutionsFundamentals of Risk Management fills a critical gap left by existing risk management texts. Instead of focusing only on quantitative risk analysis or only on institutional risk management, this book takes a comprehensive approach. The disasters of the recent financial crisis taught us that managing risk is both an art and a science, and it is critical for practitioners to understand how individual risks are integrated at the enterprise level.This book is the only resource of its kind to introduce all of the key risk management concepts in a cohesive case study spanning each chapter. A hypothetical bank drawn from elements of several real world institutions serves as a backdrop for topics from credit risk and operational risk to understanding big-picture risk exposure. You will be able to see exactly how each rigorous concept is applied in actual risk management contexts. Fundamentals of Risk Management includes: Supplemental Excel-based Visual Basic (VBA) modules, so you can interact directly with risk models Clear explanations of the importance of risk management in preventing financial disasters Real world examples and lessons learned from past crises Risk policies, infrastructure, and activities that balance limited quantitative models This book provides the element of hands-on application necessary to put enterprise risk management into effective practice. The very best risk managers rely on a balanced approach that leverages every aspect of financial operations for an integrative risk management strategy. With Fundamentals of Risk Management, you can identify and control risk at an expert level.
Online version: Rossi, Clifford. Risk professional's survival guide Hoboken, New Jersey : Wiley, 2014 9781118922378 (DLC) 2014018147
Includes index.
Keywords: Risk management; BUSINESS & ECONOMICS / Investments & Securities